Match analysis of elite female basketball during competition - Conte, D.; Minganti, C.; Tessitore, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Basketball, as team sport, has fascinated worldwide spectators with its dynamic play. However, how the time-motion is structured in a game is more known for male rather than for female competitions. Thus, the purpose of this study was to investigate the duration of live time (LT), and stoppage (ST) playing phases during official Italian female elite basketball games. Methods: To this scope three First Division championship games were continuously recorded and analyzed by a very expert match analyst. The LT was considered the actual playing time, while ST was any stoppage in play. Both LT and ST durations were classified according to 5 classes of frequency (1-20; 21-40; 41-60; 61-80; and >80 seconds). The LT phases were further classified in those entirely played on a half court and those on total court, in order to register one or more transfer (TR) phases, using 5 classes of frequency (n= 1; 2; 3; 4; >4). Chi Square was applied to investigate differences among games, and classes of frequency. Furthermore, a descriptive statistic (frequency and percentage), and LT/ST ratio was calculated. Results: No significant differences were found among matches for LT, ST and TR, while a difference was found for half court actions p<0.001. Moreover, significant differences were found among LT, ST an TR classes of frequency p<0.001. Descriptive analysis showed, both for LT and ST, higher frequency of occurrence for 1-20s (45.9%±7.7 and 49.2%±9, respectively) and 21- 40s (29.3%±3.4 and 31,7%±1,5 respectively). Furthermore, 36.2% and 63.8% of actions were played on half and total court, respectively. The TR analysis showed as 48.4% and 27.1% of TR actions were performed with 1 and 2 transfer phases, respectively. The LT/ST ratio was 1.09±0.28. Discussion: The findings of this study showed as most of the LT and ST phases lasted less than 40 seconds, with a 1:1 LT/ST ratio, and a reduced number of consecutive TR phases in actions, underlining the intermittent nature of female basketball (Matthew and Delextrat, 2009). These data could help female basketball coaches to set-up drills with a short duration and a reduced number of TR.